Individualised dietary counselling for nutritionally at‐risk older patients following discharge from acute hospital to home: a systematic review and meta‐analysis. Issue 2 (18th March 2015) - Munk, T.; Tolstrup, U.; Beck, A. M.; Holst, M.; Rasmussen, H. H.; Hovhannisyan, K.; Thomsen, T.
Abstract: Background: Many older patients are undernourished after hospitalisation. Undernutrition impacts negatively on physical function and the ability of older patients to perform activities of daily living at home after discharge from acute hospital. The present study aimed to evaluate the evidence for an effect of individualised dietary counselling following discharge from acute hospital to home on physical function, and, second, on readmissions, mortality, nutritional status, nutritional intake and quality of life (QoL), in nutritionally at‐risk older patients. Methods: A systematic review of randomised controlled trials was conducted. The overall quality of the evidence was assessed according to Grading of Recommendations Assessment, Development and Evaluation system (GRADE) criteria. Results: Four randomised controlled trials ( n  = 729) were included. Overall, the evidence was of moderate quality. Dietitians provided counselling in all studies. Meta‐analyses showed a significant increase in energy intake [mean difference (MD) = 1.10 MJ day −1, 95% confidence interval (CI) = 0.66–1.54, P  <   0.001], protein intake (MD = 10.13 g day −1, 95% CI = 5.14–15.13, P  <   0.001) and body weight (BW) (MD = 1.01 kg, 95% CI = 0.08–1.95, P  =   0.03). Meta‐analyses revealed no significant effect on physical function assessed using hand grip strength, and similarly on mortality. Narrative summation of effects on physical function using other instruments revealed inconsistent effects. Meta‐analyses were not conducted on QoL and readmissions as a result of a lack of data. Conclusions: Individualised dietary counselling by dietitians following discharge from acute hospital to home improved BW, as well as energy and protein intake, in older nutritionally at‐risk patients, although without clearly improving physical function. The effect of this strategy on physical function and other relevant clinical outcomes warrants further investigation.